PENERAPAN METODE LANGSUNG (DIRECT METHOD) DALAM PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN TA’MIRUL ISLAM SURAKARTA - Hakimuddin Salim; Muh. Nur Rochim Maksum; Deddy Ramdhani; Aimmatul Hanifah Hanifah Rosyidamalna (Universitas Muhammadiyah Surakarta, 2021)
This study aims to determine how the Direct Method is applied in learning Arabic at the Ta'mirul Islamic Islamic Boarding School in Surakarta and also the factors that support its success. There is a problem behind the researchers because the Ta'mirul Islam Islamic Boarding School has been designed to use Arabic and English as a language to communicate, practice speaking skills without using the mother tongue, and also the importance of using methods in learning, especially in the use of the Direct Method. This study uses a qualitative method with a descriptive type of research that is by observing a phenomenon to understand a symptom. This study uses the theory of Miles and Huberman, namely data analysis in 3 ways, namely: data reduction, data presentation, and conclusions. The data obtained by the researcher is by means of observation, interviews, and documentation. The results of the research that have been obtained are the application of the Direct Method (Direct Method) in learning Arabic starting from the making of the syllabus, I'dadu tadris, the process of implementing learning, and also evaluating verbally and in writing at the end of learning. The supporting factors are Factors located in the cottage environment, Arabic language teaching teachers, the selection of learning methods and media, supporting facilities and infrastructure, interest in students and motivation given by teachers, additional extracurricular activities in the cottage.